Crack path dependence on inhomogeneities of material microstructure - Roberto Brighenti; Andrea Carpinteri; Roberto Brighenti; Roberto Brighenti; Andrea Carpinteri; Andrea Spagnoli; Daniela Scorza; Andrea Carpinteri; Andrea Spagnoli; Daniela Scorza; Andrea Spagnoli; Daniela Scorza (Fracture and Structural Integrity)
Crack trajectories under different loading conditions and material microstructural features play an important role when the conditions of crack initiation and crack growth under fatigue loading have to be evaluated. Unavoidable inhomogeneities in the material microstructure tend to affect the crack propagation pattern, especially in the short crack regime. Several crack extension criteria have been proposed in the past decades to describe crack paths under mixed mode loading conditions. In the present paper, both the Sih criterion (maximum principal stress criterion) and the R-criterion (minimum extension of the core plastic zone) are adopted in order to predict the crack path at the microscopic scale level by taking into account microstress fluctuations due to material inhomogeneities. Even in the simple case of an elastic behaviour under uniaxial remote stress, microstress field is multiaxial and highly non-uniform. It is herein shown a strong dependence of the crack path on the material microstructure in the short crack regime, while the microstructure of the material does not influence the crack trajectory for relatively long cracks.